Analisis Kata Tidak Baku dalam Skripsi “Efektivitas Pengelolaan Sampah Berbasis TPS 3R di Tps Jokotole, Kelurahan Barurambat Timur, Kecamatan Pademawu, Kabupaten Pamekasan” - Lailatul Fitriyah; Jamilatul Baladiah; Mahda Annida Mufasyaroh; Hurriana Hurriana; Ana Ananda (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study analyzes the use of non-standard words in a thesis entitled "Effectiveness of Waste Management Based on Reduce, Reuse, Recycle (TPS 3R) Waste Disposal Sites at TPS Jokotole, Barurambat Timur Village, Pademawu District, Pamekasan Regency". The use of language is an essential thing in communicating, both orally and in writing to convey messages and information so that they are conveyed effectively. However, language errors are often found, especially the use of non-standard words, even by someone who has a deep understanding of Indonesian language rules. The use of standard language is very important to avoid misunderstandings, especially in the context of scientific writing such as theses. This research method uses a descriptive qualitative method with data collected then analyzed, classified, and evaluated standard and non-standard vocabulary based on KBBI. The results of this study indicate that many uses of non-standard words include errors in phonology, morphology, use of the preposition "di", punctuation, and non-standard spelling errors, as well as word wasting. These errors are mostly caused by habits, the influence of foreign languages, and a lack of understanding of standard language rules. The research findings highlight the importance of understanding the application of standard language rules in scientific writing to improve the quality of students' writing.